A Virtue Ethics Interpretation of the ‘Argument from Nature’ for Both Humans and the Environment - Nin Kirkham (Philosophies, 2024)
Appeals to the moral value of nature and naturalness are commonly used in debates about technology and the environment and to inform our approach to the ethics of technology and the environment more generally. In this paper, I will argue, firstly, that arguments from nature, as they are used in debates about new technologies and about the environment, are misinterpreted when they are understood as attempting to put forward categorical objections to certain human activities and, consequently, their real significance is often overlooked. Secondly, arguments from nature, particularly as they are used in the context of debates over the use of new technologies, can be understood as appealing to human nature as a way to determine human limitations. Thirdly, arguments from nature can inform our discussion of what it is to be a human being or a person, and this kind of discussion can, in turn, inform our ethical deliberations in such areas of bioethics as euthanasia, abortion, etc. Finally, I conclude that a proper understanding of these arguments can help in establishing which virtues and which vices relate to our relationship with the non-human world—that is, which character dispositions are relevant to an environmental virtue ethics, with human nature as its foundation. A proper understanding of the argument from nature provides the basis for a ‘virtuously anthropocentric’ environmental ethics.